Lightweight and secure vehicle track verification scheme via broadcast communication channels - Zhiqiang NING; Yuanyuan WANG; Chi ZHANG; Lingbo WEI; Nenghai YU; Yue HAO (网络与信息安全学报)
In intelligent transportation systems, it is crucial for smart vehicles to broadcast real-time vehicle track messages to coordinate driving decisions and ensure driving safety.However, attackers can manipulate vehicle tracks by modifying timestamps or manipulating signal frequencies, posing a threat to security.To address this problem, a lightweight vehicle track verification scheme was proposed, utilizing the broadcast communication channels to achieve secure verification of vehicle tracks without any special hardware support.Without time synchronization, each verifier calculated the time interval between the reception time of the message and the sending timestamp.Spatial position constraint equations are formulated by combining these time intervals between any two verifiers, effectively defending against timestamp forgery attacks.Additionally, each verifier calculates the Doppler frequency shift between the arrival frequency and the scheduled transmit frequency.Velocity vector constraint equations were formulated by combining these frequency shifts between any two verifiers, providing defense against carrier frequency manipulation attacks.Formal analysis shows that increasing the number of verifiers improves the accuracy of the proposed verification scheme.Experimental results in a real-world environment further validate that the proposed verification scheme exhibits the best performance when the number of verifiers is set to 3.Compared to the existing solution, the proposed verification scheme has a higher accuracy, lower false rejection rate, and lower false acceptance rate when validating true vehicle track and false vehicle track separately.